Essential role of EBF1 in the generation and function of distinct mature B cell types - Vilagos, Bojan (The Rockefeller University Press, 2012)
The transcription factor EBF1 is essential for lineage specification in early B cell development. In this study, we demonstrate by conditional mutagenesis that EBF1 is required for B cell commitment, pro–B cell development, and subsequent transition to the pre–B cell stage. Later in B cell development, EBF1 was essential for the generation and maintenance of several mature B cell types. Marginal zone and B-1 B cells were lost, whereas follicular (FO) and germinal center (GC) B cells were reduced in the absence of EBF1. Activation of the B cell receptor resulted in impaired intracellular signaling, proliferation and survival of EBF1-deficient FO B cells. Immune responses were severely reduced upon Ebf1 inactivation, as GCs were formed but not maintained. ChIP- and RNA-sequencing of FO B cells identified EBF1-activated genes that encode receptors, signal transducers, and transcriptional regulators implicated in B cell signaling. Notably, ectopic expression of EBF1 efficiently induced the development of B-1 cells at the expense of conventional B cells. These gain- and loss-of-function analyses uncovered novel important functions of EBF1 in controlling B cell immunity.